Pengaruh Harga dan Kualitas Produk Pintu Kamar Mandi PVC terhadap Keputusan Pembelian pada PD. Amin Makmur Sejati di Pondok Kacang Timur - Fernando, Jacky; Pasaribu, Veta Lidya Delimah (BUDGETING : Journal of Business, Management and Accounting, 2024)
The purpose of this research was to determine the effect of Price and Product Quality on buying decision at PD. Amin Makmur Sejati. The method used are quantitative-descriptive method with associative approach. The sampling technique used is Probability Sampling, sampling method using Slovin formula. Data analysis used regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are Price (X1) and Product Quality (X2) have a positive and significant effect on Buying Decision (Y) with the regression equation Y = 3,343 + 0,193X1 + 0,523X2. The coefficient of determination has a simultaneous effect of 82,1%. Hypothesis testing partially obtained Price figures of tarithmetic>ttable or (6,693 > 1,993). Then H0 is rejected and H1 is accepted. This means that there is a positive and significant influence between the independent variables, namely Price (X1) on Buying Decision (Y). Product Quality amounted to tarithmetic >ttable or (17,915 > 1,993). Then H0 is rejected and H2 is accepted. This means that there is an influence between the independent variables, namely Product Quality (X2) on buying Decision (Y). hypothesis testing obtained by the calculated fvalue >ttable or (173,544 > 2,730). Then H0 is rejected and H3 is accepted, meaning that Price (X1) and Product Quality (X2) together have a positive effect on Buying Decision (Y). Keywords: Buying Decision, Price, Product Quality.